Community Empowerment in Efforts to Prevent and Transmission of HIV/ AIDS in Sidoarjo - Erika Martining Wardani; Riezky Faisal Nugroho (Indonesia Berdaya, 2021)
HIV / AIDS is a disease that continues to grow and become a global problem that is sweeping the world. The prevalence of HIV cases according to WHO (2015) shows, the number of people with HIV numbered 17,325 people and AIDS was recorded at 1,238 people. Therefore, people need to know about HIV / AIDS and its dangers so as to be able to prevent the transmission of the disease properly, it is necessary to provide appropriate health education to overcome these problems. This community service activity aims to increase public knowledge about HIV / AIDS and the prevention and transmission of HIV / AIDS. The level of public knowledge is measured by conducting a pre-test by filling out a questionnaire before being given health education and post-test after being given health education. The level of mother's knowledge can be measured by comparing the results of pre-test and post-test. Based on the pre-test results followed by 50 respondents. The statistical test results obtained p = 0.001, meaning that there is a significant difference between public knowledge before and after being given health education about the prevention and transmission of HIV / AIDS. The results of community service are expected to improve the health status in the Jemirahan Village community, Jabon District, Sidoarjo Regency, especially for the prevention and transmission of HIV / AIDS.